Transition to democracy in Eastern Europe - Beyme, Klaus von (Advances in Political Science: An International Series, 1996)
This is the first comprehensive study of the transition to democracy in Eastern Europe which includes the processes in party-formation, political culture-building, institution-building and economic transformation, and to differentiate between areas and countries. East and southeastern Europe are included as well as the Republics of the former Soviet Union. The theories of transformation to democracy developed in former transitions, such as 1919, 1945 and the 1970s are tested in the case of Eastern Europe. In many areas the picture developed by the author is not very optimistic. He feels that 'Anocracy', a mixture between democracy and authoritarian regimes, is likely to develop in many countries